PROGRAM DESA TANGGUH COVID-19 DI DESA PIKAT KABUPATEN KLUNGKUNG PROVINSI BALI - Luh Seri Ani; Ni Wayan Arya Utami; IGA Sri Darmayani; I Made Merdana; I Komang Ari Mogi (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The Covid-19 pandemic caused health problems in various countries including Indonesia. Various efforts have been made as a strategy to prevent the transmission of Covid-19 including the implementation of restriction on community activity to reduce mobility, implementing health protocols, namely wearing masks, social distancing, washing hands, tests, search, follow-up, and vaccinations.  The Covid-19 resilient village program was organized to raise public awareness about covid-19 infections and how to maintain physical and mental health. The Covid-19 resilient village program was implemented in Pikat Village, Klungkung Regency, Bali Province. The activity took place in July-August 2021. The target of the activity is the entire community in Pikat Village. The activity was carried out by a combination method online and offline in related the Covid-19 pandemic situation and the implementation of restrictions on activities for all communities including in Pikat Village. The Covid-19 resilient village program consists of 5 activities, namely Covid-19 contact trackers, mask waste processing education, mental health education, benefits education as an immunity-enhancing material, distribution of masks and handsanitizers for the community. This activity runs smoothly and provides benefits for the community so that it needs to be maintained the continuity of activities to educate the community in accordance with needs.